Infected Pancreatic Hydatid Cyst with Cysto-Pancreatic Fistula Presenting as Acute Pancreatitis - Daniel, Phillip; Shukla, Siddharth; Prabhakar, Nidhi; Kulkarni, Aditya; Sharma, Ravi; Gupta, Rajesh; Rana, Surinder Singh (Journal of Digestive Endoscopy, 2019)
Hydatid cysts can be found in almost any organ of the body with the most common sites being liver, lung, spleen, and kidney. A pancreatic hydatid cyst is rare but an isolated pancreatic hydatid cyst is even rarer. Cysts in the head of pancreas usually present with jaundice, whereas cysts located in the body and tail are usually asymptomatic. We present a rare case of isolated pancreatic hydatid cyst that presented with acute pancreatitis and mimicked a pancreatic fluid collection.
Keywords: cysts; endosonography; hydatid; pancreatitis